Сучасні тенденції виробництва вогнетривів на основі кварцу для коксових печей - Немсадзе, Г.Г.; Тонкушин, А.Ф. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to the issues of coke production, as an important component of the metallurgical cycle of pig iron producing. The analysis of the problems arising in the technological process of coke production with given parameters in coke oven batteries, taking into account their design features is carried out. The importance of the quality of refractory dinas and chamotte products, the condition of the lining of the batteries in ensuring their stability at high temperatures and its sharp drops when loading coal and the production of hot coke, as well as chemical resistance to aggressive coal tar and gases is determined. The prospects of using quartzite as a basis for lining, taking into account its high service characteristics, are noted. At the same time, the difficulties of its processing due to volumetric changes in materials based on it during heating are considered. It is proposed to use plasma remelting of pure quartz sand at temperatures above 1750 °C, which will ensure stabilization of the quartz structure. This allows the production of refractory products based on fused silica for coke oven batteries, which retain their size at high temperatures without loss of strength. It is noted that the new method for the production of such refractories eliminates a number of technological processes, such as pressing and long-term firing in tunnel kilns, characteristic of dinas refractories. The new material also allows you to design block-type linings, drastically reduce the time of lining operations and allows them to be mechanized as much as possible.